Die Sammlung Essl. - Bösch, Gabriele; Exhibition. Die Sammlung Essl. Sammlung Essl Kunst der Gegenwart Klosterneuburg (Wien). 1998 (Klosterneuburg (Wien) : Sammlung Essl Kunst der Gegenwart Klosterneuburg (Wien), 1998)
Kolig, Anton ; Jorn, Asger ; Brandl, Herbert ; Kowanz, Brigitte ; Baselitz, Georg ; Rainer, Arnulf ; Weiler, Max ; Prachensky, Markus ; Lassnig, Maria ; West, Franz ; Anzinger, Siegfried ; Moll, Carl ; Hundertwasser ; Kogelnik, Kiki ; Thöny, Wilhelm ; Ringel, Franz ; Kogler, Peter ; Nitsch, Hermann ; Attersee, Christian Ludwig ; Kandl, Johanna ; Brus, Günter
Duits
boek
Keywords: Klosterneuburg